Male and female reproductives are potential sources of RNA virus dissemination in Solenopsis invicta - Steven M. Valles; Roxie L. White; Quentin D. Read (Journal of Invertebrate Pathology, 2026)

Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Evaluation of organosilicone surfactants as synergists of Solenopsis invicta virus 3 in Solenopsis invicta - Roxie L. White; Quentin D. Read; Steven M. Valles (Journal of Invertebrate Pathology, 2026)

Stock Identity of Stranded Tamanend's Bottlenose Dolphins ( Tursiops erebennus ) With Evidence of Fisheries Interaction in Virginia, North Carolina, and South Carolina, 1996–2019 - Kim W. Urian; Susan G. Barco; Karen L. Clark; Alex M. Costidis; Paul Doshkov; Marina Piscitelli‐Doshkov; Alexandra L. Epple; Tiffany F. Keenan; William A. McLellan; Wayne E. McFee; D. Ann Pabst; Keith A. Rittmaster; et al. (Marine Mammal Science, 2026)
The complex population structure of Tamanend's bottlenose dolphins ( Tursiops erebennus ) along the U.S. Mid‐Atlantic coast complicates assessment of their bycatch. To improve our understanding of the stock identity of individual dolphins taken as bycatch in this region, we compared images of the dorsal fins of bottlenose dolphins that stranded with evidence of fishery interactions (FI+) to the Mid‐Atlantic Bottlenose Dolphin Catalog (MABDC). We obtained stranding data from NOAA Fisheries for 715 FI+ bottlenose dolphins from Virginia (VA), North Carolina (NC), and South Carolina (SC) from 1996 to 2019; approximately two thirds of these records included dorsal fin images. For records for which images were available, we applied restrictive criteria for image quality and dorsal fin distinctiveness and compared the remaining 145 distinctive FI+ individuals to the MABDC. We matched 18 dolphins to regional catalogs and assigned stock identity to 13 of the matches; two were from migratory coastal stocks and 11 were from small estuarine stocks in NC and SC. Our analysis demonstrates how the risk of bycatch varies across bottlenose dolphin stocks along the Mid‐Atlantic coast, provides an important feedback information loop to stranding responders and researchers studying dolphins in the field, and informs conservation efforts to address bycatch of bottlenose dolphins in this region.

Socioecological determinants of dog ownership in Mara region, Tanzania - Danni Anderson; Maganga Sambo; Ahmed Lugelo; Anna Czupryna; Joel Changalucha; Jonathan M. Read; Felix Lankester; Katie Hampson (Preventive Veterinary Medicine, 2026)

Wild sources for host plant resistance to Bemisia tabaci in watermelon: insights from behavioral and chemical analyses - Petrina McKenzie-Reynolds; Isiaka A. Owolabi; Anju Biswas; Quentin D. Read; Gaelen R. Burke; Amnon Levi; Alvin M. Simmons (Crop Protection, 2026)

Australia’s forest-dwelling vascular plant and vertebrate species, their threats, and change over time: Indicators for continental-scale biodiversity assessment - Annisa Satyanti; Steve M. Read (Forest Ecology and Management, 2025)

Complex population structure revealed using genomic data from Tamanend’s bottlenose dolphins (Tursiops erebennus) - Nicole L. Vollmer; Lynsey A. Wilcox Talbot; Antoinette M. Gorgone; Aleta Hohn; Andrew J. Read; Eric S. Zolman; Patricia E. Rosel (Marine Biology, 2025)
In the waters of North Carolina, on the United States east coast, Tamanend’s bottlenose dolphin ( Tursiops erebennus ) is managed as four stocks, differentiated largely based on photo-identification and satellite telemetry data. Two of the stocks reside primarily within estuarine habitats throughout the year, and two others inhabit coastal waters and make broad scale, migratory movements. The spatio-temporal overlap of these stocks in North Carolina varies seasonally, creating a complicated scenario in which stock boundaries are difficult to identify, and the demographic independence among groups is not well understood. Furthermore, incidental mortality and serious injury of dolphins occurs in several North Carolina fisheries, but the spatio-temporal overlap of the four stocks makes it difficult to assign mortalities and characterize their impact on each stock. To investigate population structure in this complex environment, we obtained biopsy samples from Tamanend’s bottlenose dolphins, and utilized next-generation molecular sequencing to produce a data set of over 6,000 single nucleotide polymorphism markers. Cluster and migration analyses supported the presence of four demographically independent populations. However, the distributions of these populations do not align well with the currently delineated stocks. Instead, our analyses support the existence of three populations in estuarine waters of North Carolina and one inhabiting coastal waters. An improved understanding of the underlying population structure of Tamanend’s bottlenose dolphins in these waters will provide a better characterization of stock distribution and support more accurate assignment of mortality, which is necessary for successful conservation and management of this species.

Structural and developmental insights into the muscles involved in lionfish ( Pterois spp.) vocalisations - Roxanne B. Holmes; Nadia M. Hamilton; Katharine E. Criswell; Keturah Z. Smithson; James E. Herbert‐Read; Lucille Chapuis (Journal of Fish Biology, 2025)
Vocal signalling is an important mode of communication in fishes. The two species of lionfish in the Pterois complex, the Indo‐Pacific lionfish ( Pterois volitans) and the red lionfish ( Pterois miles ), are both known to produce different types of sounds with sonic muscles attached to the swimbladder. However, the specific mechanism and the functions of these vocalisations in these invasive species are still unknown. We used three‐dimensional bioimaging to describe the anatomy of the sonic muscles of both species. We further quantified the muscles of P. volitans to specifically explore how muscles developed across ontogeny and to test the hypothesis that sonic muscles would show sexual dimorphism if they were a sexually selected trait. Both P. volitans and P. miles showed a physoclistous swimbladder with a bilaterally symmetric pair of extrinsic sonic swimbladder muscles (ESSMs), which have been suggested to control buoyancy and generate vocalisations. Both species also displayed an additional pair of anterior extrinsic muscles, which projected dorsoventrally from the spinal column and inserted onto the anterior wall of the swimbladder, potentially also having a role in sound production. Both types of sonic muscles were present across ontogeny. Quantification of the posterior belly of the ESSMs in P. volitans showed that both the length and mass of these muscles in both mature and immature individuals increased linearly with body size. There were no ontogenetic or sex differences in sonic muscle investment between individuals. Given the primary function of these muscles is to control the swimbladder for buoyancy, this may constrain the modification of these muscles relative to body size, or they may have no differences in their acoustic function between sexes or across ontogeny.

Virome of Solenopsis invicta (Hymenoptera: Formicidae): Intercontinental differences in the native and introduced ranges - Steven M. Valles; Marina S. Ascunce; Quentin D. Read; Roxie L. White; Robert K. Vander Meer (Journal of Invertebrate Pathology, 2025)

A standardized nontargeted metabolomics method for cross-laboratory comparison of food profiles - Melanie T. Odenkirk; Cole Michel; Katrina A. Doenges; Katrina L. Leaptrot; Stacy D. Sherrod; Jody C. May; Margaret L. Read; Jacqueline M. Chaparro; Nathan Montgomery; Sarah Brinkley; Arpana Vaniya; Susan B. Mitchell; et al. (Food Chemistry, 2025)

Wastewater surveillance of SARS-CoV-2 and influenza in a dynamic university community: understanding how wastewater measurements correspond to reported cases - Matthew J. Jones; Rukayya Ibrahim; Shirley Clark; Yolanda M. Brooks; Heather E. Preisendanz; Thomas L. Richard; Andrew F. Read; Courtney J. Robinson; Samina Noorali; Michael J. Shreve; Nina L. Dennington; Justin D. Silverman; et al. (Science of The Total Environment, 2025)

Nano-carrier, design, synthesis, in silico ADMET, anti-proliferative assessments and docking of [1,2,4]triazolo[4,3-a]quinoxalines as Topo-II inhibitors and DNA intercalators - Ahmed K. B. Aljohani; Sara A. Almadani; Marwa Alsulaimany; Naif Aljuhani; Waad A. Samman; Adel H. Al-Shareef; Read Alghamdi; Saeed M. Tayeb; Hussam Y. Alharbi; Majed S. Aljohani; Khaled El‐Adl; Mo’men Salem (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

How old are lherzolitic diamonds? Mesoproterozoic diamond formation in the root of the Sask craton - Sarah E. M. Milne; Suzette Timmerman; Kristina Kublik; Anetta Banas; Thomas Stachel; George Read; D. Graham Pearson (Mineralogy and Petrology, 2025)

Diamonds from Fort à la Corne – post-Archean formation in exceptionally cool and fertile lherzolitic substrates - Anetta Banas; Sarah E. M. Milne; Thomas Stachel; Richard A. Stern; D. Graham Pearson; George H. Read (Mineralogy and Petrology, 2025)

The Impact of Disturbance on Tree Size Distributions in the United States - Adam J. Eichenwald; John M. Grady; Jonathan A. Knott; Quentin D. Read; J. Marcos Rodriguez; Sydne Record (Global Ecology and Biogeography, 2025)
Aim Tree size distributions are an emergent feature of forest dynamics across space and time. Theory suggests that undisturbed forests exhibit a size‐abundance distribution captured by a power‐law relationship with a near‐2 slope. We aimed to quantify how disturbances systematically and predictably cause deviations from this expected pattern. Location Contiguous United States. Time Period 2001–2023. Major Taxa Studied Diverse tree communities. Methods We analysed size‐abundance distributions in over 160,000 FIA plots for both disturbed and undisturbed forests, examining changes in slope associated with disturbances, stand age, and maximum tree height. We used a Structural Equation Model (SEM) to evaluate whether disturbance effects on size‐abundance slopes were indirectly mediated by changes in stand age or maximum height. Results We found that the predominant disturbances across the dataset (e.g., ground fires, animal damage) result in predictable flattening of size‐abundance slopes, reflecting the selective removal of smaller trees. In contrast, many disturbances (e.g., wind, disease) did not shift the slopes predictably, indicating that they did not selectively impact any specific size class. Maximum tree height and stand age were also reliable predictors of size‐abundance distributions, but a structural equation model demonstrated that the impact of disturbance on size‐abundance slopes was not mediated through its indirect effects on stand age or maximum tree height, suggesting a direct pathway of influence. Main Conclusions Disturbances result in predictable changes to forest size‐abundance slopes. As climate change and increased disturbance frequencies produce younger and shorter forests, future size‐abundance slopes are expected to be steeper than those in undisturbed forests. Our findings suggest a temporary flattening in the size‐abundance relationship immediately after the predominant disturbances across the dataset (ground fires, animal damage). These findings underscore the importance of understanding disturbance impacts on forest size structure to improve predictions of forests across broad spatial and temporal scales.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Active interactions between animals and technology: biohybrid approaches for animal behaviour research - M. Papadopoulou; M. Ball; P. Bartashevich; A.L.J. Burns; V. Chiara; M.A. Clark; B.R. Costelloe; M. Fele; F. French; S. Hauert; M.K. Heinrich; J.E. Herbert-Read; et al. (Animal Behaviour, 2025)

Associations of anthropogenic activity and tributaries with the physicochemical, nutrient and microbial composition of the Ganga (Ganges) River, India - Gillian E. Clayton; Laura A. Richards; Bethany G. Fox; Robin M.S. Thorn; Michael J. Bowes; Daniel S. Read; Holly J. Tipper; Kieran Khamis; Tapan K. Dutta; Arun Kumar; Moushumi Hazra; Ben Howard; et al. (Water Research, 2025)

Repeated Mitochondrial Capture With Limited Genomic Introgression in a Lizard Group - Wesley J. Read; Rebecca J. Laver; Ching Ching Lau; Craig Moritz; Stephen M. Zozaya (Molecular Ecology, 2025)
Mitochondrial introgression is common among animals and is often first identified through mitonuclear discordance—discrepancies between evolutionary relationships inferred from mitochondrial DNA (mtDNA) and nuclear DNA (nuDNA). Over recent decades, genomic data have also revealed extensive nuclear introgression in many animal groups, with implications for genetic and phenotypic diversity. However, the extent to which mtDNA introgression corresponds to nuDNA introgression varies. Here, we investigated historical and recent introgression in the Gehyra nana ‐occidentalis clade, a complex group of Australian geckos with documented cases of mitonuclear discordance suggestive of repeated mtDNA introgression. We hypothesised that mitonuclear discordance in this clade reflects mtDNA introgression with substantial nuclear introgression. Despite evidence of repeated mtDNA introgression, however, we found little to no evidence of historical nuDNA introgression using exon capture and genome‐wide single nucleotide polymorphism (SNP) data. We also found no evidence of gene flow at modern contact zones and detected only a single early generation hybrid. Unsurprisingly, given these results, we found no evidence of transgressive, intermediate, or more variable morphological phenotypes in taxa with introgressed mtDNA. These findings suggest that hybridisation in this system has, at least in some cases, resulted in repeated mitochondrial introgression with little or no nuclear introgression. This pattern aligns with other studies showing limited nuDNA introgression in taxa with mitonuclear discordance, highlighting a potentially broader trend in animal radiations.

Overwintering humpback whales adapt foraging strategies to shallow water environments at the mouth of the Chesapeake Bay, Virginia, USA - Jeanne M. Shearer; Heather J. Foley; Zachary T. Swaim; Vincent M. Janik; Andrew J. Read (Marine Mammal Science, 2025)
Some humpback whales from the Northwestern Atlantic population forgo migration to the Caribbean, spending winter months feeding along the U.S. mid‐Atlantic coast. We studied the foraging behavior of these whales at the mouth of the Chesapeake Bay, Virginia during winter from 2017 to 2022. While shipping channels here reach depths of up to 30 m, most of the area is 11–15 m deep. This shallow‐water environment poses physical constraints on classical humpback whale feeding modes. We deployed 20 digital acoustic tags (DTAGs) on humpback whales and identified foraging lunges from accelerometer data, detecting 788 lunges from 10 animals. Tagged whales averaged a single lunge per dive, lunging primarily in a horizontal orientation, with limited maneuvering compared to other study sites. Our results indicate that some elements of humpback whale foraging behavior are conserved across environments, but that the shallow depths in our study area constrain how animals are able to feed. The relatively high lunge rates we observed suggest this area is an important foraging ground. However, foraging in shipping channels increases the risk of ship strikes, which frequently occur in this area.

A horizon scan of biological conservation issues for 2025 - William J. Sutherland; Peter N.M. Brotherton; Holly M. Butterworth; Stewart J. Clarke; Tammy E. Davies; Nigel Doar; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jonathan Hughes; et al. (Trends in Ecology & Evolution, 2025)

Lionfish (Pterois volitans) do not show directional preferences for ambient underwater soundscapes during diurnal hours - Roxanne B Holmes; Nadia M. Hamilton; Stephen D. Simpson; James E. Herbert-Read (Marine Biology, 2025)
Sound is a valuable cue in the marine environment that can inform animals about habitat location and community composition. Indeed, sound is often used for orientation and navigation by larval reef fishes during settlement. However, despite sound’s role in the early life of reef fishes, whether post-settlement reef fishes use ambient soundscapes to inform their movement decisions remains less clear. In an in-situ playback experiment in Curaçao, the Dutch Caribbean, settled individuals of an invasive predator, the Indo-Pacific lionfish ( Pterois volitans ), showed no preference to move towards the playbacks of two different habitat types during daylight hours. In particular, lionfish did not prefer to move towards the sounds of sandy or reef habitat playbacks when tested against a silent control. Moreover, when given a choice between simultaneous sandy and reef habitat playbacks, lionfish showed no preference for the soundscape of either habitat type. While the activity of lionfish was strongly correlated with their body size, with larger fish being more active, activity was not affected by habitat playback, nor did body size affect their preference for the soundscapes of either habitat type. While acoustic lures have been speculated to be a promising addition to existing lionfish trap designs, daytime playbacks of ambient soundscapes are unlikely to be successful in attracting lionfish post-settlement, ultimately affecting their efficacy.

Presence of emerging organic contaminants and microbial indicators in surface water and groundwater in urban India - Bentje Brauns; Subhash Chandra; Wayne Civil; Dan J. Lapworth; Alan M. MacDonald; Andrew A. McKenzie; Daniel S. Read; Muddu Sekhar; Andrew C. Singer; Amritha Thankachan; Holly J. Tipper (Environmental Pollution, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Song fragments recorded on a tagged juvenile humpback whale ( Megaptera novaeangliae ) on a winter feeding ground at the mouth of the Chesapeake Bay, Virginia, USA - Dana L. Adcock; Jeanne M. Shearer; Heather J. Foley; Zach T. Swaim; Andrew J. Read (Marine Mammal Science, 2024)

A call to rename Ziphius cavirostris the goose‐beaked whale: promoting inclusivity and diversity in marine mammalogy by re‐examining common names - Ashley D. Rogers; Aileen Lavelle; Robin W. Baird; Arona Bender; Anna Borroni; Gustavo Cárdenas Hinojasa; William R. Cioffi; Brianna W. Elliott; Craig Harms; Anne E. Harshbarger; Ann‐Marie Jacoby; Kathryn Lienhard; et al. (Marine Mammal Science, 2024)

Predicting river phytoplankton blooms and community succession using ecological niche modeling - Michael J. Bowes; Michael G. Hutchins; David J. E. Nicholls; Linda K. Armstrong; Peter M. Scarlett; Monika D. Jürgens; Nuria Bachiller‐Jareno; Isabelle Fournier; Daniel S. Read (Limnology and Oceanography, 2024)
Excessive phytoplankton concentrations in rivers can result in the loss of plant and invertebrate communities, and threaten drinking water supplies. Whilst the physicochemical controls on algal blooms have been identified previously, how these factors combine to control the initiation, size, and cessation of blooms in rivers is not well understood. We applied flow cytometry to quantify diatom, chlorophyte, and cyanobacterial group abundances in the River Thames (UK) at weekly intervals from 2011 to 2022, alongside physicochemical data. A niche modeling approach was used to identify thresholds in water temperature, flow, solar radiation, and soluble reactive phosphorus (SRP) concentrations required to produce periods of phytoplankton growth, with blooms only occurring when all thresholds were met. The thresholds derived from the 2011 to 2018 dataset were applied to a test data set (2019–2022), which predicted the timing and duration of blooms at accuracies of > 80%. Diatoms and nano‐chlorophyte blooms were initiated by flow and water temperature, and usually terminated due to temperature and flow going out of the threshold range, or SRP and Si becoming limiting. Cyanobacterial bloom dynamics were primarily controlled by water temperature and solar radiation. This simple methodology provides a key understanding of phytoplankton community succession and inter‐annual variation and can be applied to any river with similar water quality and phytoplankton data. It provides early warnings of algal and cyanobacterial bloom timings, which support future catchment management decisions to safeguard water resources, and provides a basis for modeling changing phytoplankton bloom risk due to future climate change.

Fate and behaviour of Microplastics (> 25µm) within the water distribution network, from water treatment works to service reservoirs and customer taps - Gbotemi A. Adediran; Ruairidh Cox; Monika D. Jürgens; Elise Morel; Richard Cross; Heather Carter; M. Glória Pereira; Daniel S. Read; Andrew C. Johnson (Water Research, 2024)

The foraging ecology of green turtles (Chelonia mydas) in New Caledonia - Tyffen C. Read; Laurent Wantiez; Florent Keller; Jonathan M. Werry; Jason P. van de Merwe; Justin J. Meager; Olivier Chateau; Richard Farman; Colin J. Limpus (Marine Biology, 2024)
Green sea turtles ( Chelonia mydas ) face many threats from anthropogenic activity and are listed as Endangered on the International Union for the Conservation of Nature (IUCN) Red List of Threatened Species. They spend the majority of their lives in coastal foraging areas, and show strong fidelity to narrow foraging ranges. Understanding the foraging ecology of green turtles is therefore important for their management and conservation. Using stable isotopes analysis ( n = 200) and identification of stomach contents ( n = 21), this study investigated the foraging ecology of four distinct green turtle foraging aggregations (Goro, Isle of Pines, Ouen Island and Uo/Mato Islands) within the Grand Lagon Sud. This World Heritage Area located in New Caledonia supports regionally important nesting and foraging green turtle populations. The δ 13 C and δ 15 N values of skin samples ranged from − 19.3 to − 7.3‰ and 2.8–15.9‰, respectively. Metrics of isotopic niche and regression analyses were used to assess the degree of omnivory, trophic diversity and potential ontogenetic diet shifts in the different aggregations of foraging green turtles in this location. Each of the four sites and four age-classes had distinct isotopic niches, with evidence of omnivory and ontogenetic shifts, particular in new recruits and juveniles, and at Goro and Uo/Mato Islands. This was generally supported by the stomach contents analyses of a small number of green turtles opportunistically sampled from traditional ceremonies. This study provides important information on the foraging ecology of green turtles in New Caledonia, supporting management outcomes in this region. This collaboration with the tribes of the Grand Lagon Sud is also the first step towards the integrated management of the resource.

Introducing Elinor for monitoring the governance and management of area‐based conservation - Shauna L. Mahajan; Samson Obiene; Lenice Ojwang; Nasser Olwero; Abel Valdivia; Adaoma Wosu; Emily Adrid; Dominic A. Andradi‐Brown; Gildas Andriamalala; Natalie C. Ban; Nathan J. Bennett; Jessica Blythe; et al. (Conservation Biology, 2024)
Monitoring the governance and management effectiveness of area‐based conservation has long been recognized as an important foundation for achieving national and global biodiversity goals and enabling adaptive management. However, there are still many barriers that prevent conservation actors, including those affected by governance and management systems from implementing conservation activities and programs and from gathering and using data on governance and management to inform decision‐making across spatial scales and through time. We explored current and past efforts to assess governance and management effectiveness and barriers actors face in using the resulting data and insights to inform conservation decision‐making. To help overcome these barriers, we developed Elinor, a free and open‐source monitoring tool that builds on the work of Nobel Prize winner Elinor Ostrom to facilitate the gathering, storing, sharing, analyzing, and use of data on environmental governance and management across spatial scales and for areas under different governance and management types. We consider the process of codesigning and piloting Elinor with conservation scientists and practitioners and the main components of the assessment and online data system. We also consider how Elinor complements existing approaches by addressing governance and management in a single assessment at a high level for different types of area‐based conservation, providing flexible options for data collection, and integrating a data system with an assessment that can support data use and sharing across different spatial scales, including global monitoring of the Global Biodiversity Framework. Although challenges will continue, the process of developing Elinor and the tool itself offer tangible solutions to barriers that prevent the systematic collection and use of governance and management data. With broader uptake, Elinor can play a valuable role in enabling more effective, inclusive, and durable area‐based conservation.

A horizon scan of global biological conservation issues for 2024 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Stuart H.M. Butchart; Holly M. Butterworth; Stewart J. Clarke; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice C. Hughes; Jennifer James; et al. (Trends in Ecology & Evolution, 2024)

Global taxonomic, functional, and phylogenetic diversity of bees in apple orchards - N. Leclercq; L. Marshall; T. Weekers; P. Basu; D. Benda; D. Bevk; R. Bhattacharya; P. Bogusch; A. Bontšutšnaja; L. Bortolotti; N. Cabirol; E. Calderón-Uraga; et al. (Science of The Total Environment, 2023)

Preliminary assessment of bacterial antibiotic resistance and Candidatus Liberibacter asiaticus titer in three Florida commercial citrus groves - Marie de Gracia Coquerel; Jieli Wegerif; Andrew McAuley; Quentin D. Read; Nabil Chowdhury; Kwang Cheol Jeong; J. Glenn Morris; Samuel J. Martins; Erica M. Goss; Marina S. Ascunce (Crop Protection, 2023)

Hypoxia Interrupts the Secondary Production Service Provided by Oyster Reef Macrofauna in Mississippi Sound, USA - Chet F. Rakocinski; J. Read Hendon; Kathy E. VanderKooy; Jeremy M. Higgs; Virginia R. Schweiss; Scott C. McIntosh; Daneen P. Menke (Estuaries and Coasts, 2023)

Targeting and image acquisition of Martian surface features with TGO/CaSSIS - M. Almeida; M. Read; N. Thomas; G. Cremonese; P. Becerra; G. Borrini; S. Byrne; M. Gruber; R. Heyd; C.M. Marriner; G. McArthur; A.S. McEwen; et al. (Planetary and Space Science, 2023)

Establishing effective conservation management strategies for a poorly known endangered species: a case study using Australia’s Night Parrot (Pezoporus occidentalis) - Nicholas P. Leseberg; Alex Kutt; Megan C. Evans; Tida Nou; Scott Spillias; Zoe Stone; Jessica C. Walsh; Stephen A. Murphy; Mike Bamford; Allan H. Burbidge; Kate Crossing; Robert A. Davis; et al. (Biodiversity and Conservation, 2023)
An evidence-based approach to the conservation management of a species requires knowledge of that species’ status, distribution, ecology, and threats. Coupled with budgets for specific conservation strategies, this knowledge allows prioritisation of funding toward activities that maximise benefit for the species. However, many threatened species are poorly known, and determining which conservation strategies will achieve this is difficult. Such cases require approaches that allow decision-making under uncertainty. Here we used structured expert elicitation to estimate the likely benefit of potential management strategies for the Critically Endangered and, until recently, poorly known Night Parrot ( Pezoporus occidentalis ). Experts considered cat management the single most effective management strategy for the Night Parrot. However, a combination of protecting and actively managing existing intact Night Parrot habitat through management of grazing, controlling feral cats, and managing fire specifically to maintain Night Parrot habitat was thought to result in the greatest conservation gains. The most cost-effective strategies were thought to be fire management to maintain Night Parrot habitat, and intensive cat management using control methods that exploit local knowledge of cat movements and ecology. Protecting and restoring potentially suitable, but degraded, Night Parrot habitat was considered the least effective and least cost-effective strategy. These expert judgements provide an informed starting point for land managers implementing on-ground programs targeting the Night Parrot, and those developing policy aimed at the species’ longer-term conservation. As a set of hypotheses, they should be implemented, assessed, and improved within an adaptive management framework that also considers the likely co-benefits of these strategies for other species and ecosystems. The broader methodology is applicable to conservation planning for the management and conservation of other poorly known threatened species.

A surplus no more? Variation in krill availability impacts reproductive rates of Antarctic baleen whales - Logan J. Pallin; Nick M. Kellar; Debbie Steel; Natalia Botero‐Acosta; C. Scott Baker; Jack A. Conroy; Daniel P. Costa; Chris M. Johnson; David W. Johnston; Ross C. Nichols; Doug P. Nowacek; Andrew J. Read; et al. (Global Change Biology, 2023)
The krill surplus hypothesis of unlimited prey resources available for Antarctic predators due to commercial whaling in the 20th century has remained largely untested since the 1970s. Rapid warming of the Western Antarctic Peninsula (WAP) over the past 50 years has resulted in decreased seasonal ice cover and a reduction of krill. The latter is being exacerbated by a commercial krill fishery in the region. Despite this, humpback whale populations have increased but may be at a threshold for growth based on these human‐induced changes. Understanding how climate‐mediated variation in prey availability influences humpback whale population dynamics is critical for focused management and conservation actions. Using an 8‐year dataset (2013–2020), we show that inter‐annual humpback whale pregnancy rates, as determined from skin‐blubber biopsy samples ( n = 616), are positively correlated with krill availability and fluctuations in ice cover in the previous year. Pregnancy rates showed significant inter‐annual variability, between 29% and 86%. Our results indicate that krill availability is in fact limiting and affecting reproductive rates, in contrast to the krill surplus hypothesis. This suggests that this population of humpback whales may be at a threshold for population growth due to prey limitations. As a result, continued warming and increased fishing along the WAP, which continue to reduce krill stocks, will likely impact this humpback whale population and other krill predators in the region. Humpback whales are sentinel species of ecosystem health, and changes in pregnancy rates can provide quantifiable signals of the impact of environmental change at the population level. Our findings must be considered paramount in developing new and more restrictive conservation and management plans for the Antarctic marine ecosystem and minimizing the negative impacts of human activities in the region.

Indicators of the effects of climate change on freshwater ecosystems - Kevin C. Rose; Britta Bierwagen; Scott D. Bridgham; Daren M. Carlisle; Charles P. Hawkins; N. LeRoy Poff; Jordan S. Read; Jason R. Rohr; Jasmine E. Saros; Craig E. Williamson (Climatic Change, 2023)

A global biological conservation horizon scan of issues for 2023 - William J. Sutherland; Craig Bennett; Peter N.M. Brotherton; Holly M. Butterworth; Mick N. Clout; Isabelle M. Côté; Jason Dinsdale; Nafeesa Esmail; Erica Fleishman; Kevin J. Gaston; James E. Herbert-Read; Alice Hughes; et al. (Trends in Ecology & Evolution, 2023)

Low-cost soybean input bundles impact women farmers’ subsistence livelihood traps: evidence from Ghana - Kathleen Ragsdale; Mary R. Read-Wahidi; Qian M. Zhou; Kerry Clark; Mawuli A. K. Asigbee; Courtney Tamimie; Peter Goldsmith (Food Security, 2022)
The Soybean Uptake and Network Survey was administered to a random sample of 832 smallholder male and female farmers in northern Ghana to explore gender and other factors related to soybean production. We investigated the effect of receiving a Soybean Success Kit (i.e., certified seed, fertilizer, inoculum) on soybean yield and income from soybean, controlling for factors such as gender. This analysis includes farmers who 1) resided in districts where Kits were distributed, 2) planted soybean in the past 12 months, and 3) for whom we had complete information for district and gender ( n = 371). When results were disaggregated by gender among Kit recipients, average soybean yield (ASY) for males was 108% and average soybean income (ASI) was 97% of that for females. When results were disaggregated by gender among Kit non-recipients, ASY for males was 142% and ASI was 147% of that for females. When results for males were disaggregated by whether the respondent received a Kit, ASY for male Kit recipients was 113% and ASI was 112% of that for male non-recipients. When results for females were disaggregated by whether the respondent received a Kit, ASY for female Kit recipients was 148% and ASI was 170% of that for female non-recipients. These results suggest that providing smallholder female farmers with access to low-cost (˂USD6) input bundles to which they customarily have little or no access can help eliminate the gender gap in agricultural productivity. These results may be applicable to other sub-Saharan Africa countries, where targeting smallholder female farmers as input bundle beneficiaries may positively impact agricultural productivity.

Towards mapping biodiversity from above: Can fusing lidar and hyperspectral remote sensing predict taxonomic, functional, and phylogenetic tree diversity in temperate forests? - Aaron G. Kamoske; Kyla M. Dahlin; Quentin D. Read; Sydne Record; Scott C. Stark; Shawn P. Serbin; Phoebe L. Zarnetske (Global Ecology and Biogeography, 2022)
Aim Rapid global change is impacting the diversity of tree species and essential ecosystem functions and services of forests. It is therefore critical to understand and predict how the diversity of tree species is spatially distributed within and among forest biomes. Satellite remote sensing platforms have been used for decades to map forest structure and function but are limited in their capacity to monitor change by their relatively coarse spatial resolution and the complexity of scales at which different dimensions of biodiversity are observed in the field. Recently, airborne remote sensing platforms making use of passive high spectral resolution (i.e., hyperspectral) and active lidar data have been operationalized, providing an opportunity to disentangle how biodiversity patterns vary across space and time from field observations to larger scales. Most studies to date have focused on single sites and/or one sensor type; here we ask how multiple sensor types from the National Ecological Observatory Network’s Airborne Observation Platform (NEON AOP) perform across multiple sites in a single biome at the NEON field plot scale (i.e., 40 m × 40 m). Location Eastern USA. Time period 2017–2018. Taxa studied Trees. Methods With a fusion of hyperspectral and lidar data from the NEON AOP, we assess the ability of high resolution remotely sensed metrics to measure biodiversity variation across eastern US temperate forests. We examine how taxonomic, functional, and phylogenetic measures of alpha diversity vary spatially and assess to what degree remotely sensed metrics correlate with in situ biodiversity metrics. Results Models using estimates of forest function, canopy structure, and topographic diversity performed better than models containing each category alone. Our results show that canopy structural diversity, and not just spectral reflectance, is critical to predicting biodiversity. Main conclusions We found that an approach that jointly leverages spectral properties related to leaf and canopy functional traits and forest health, lidar derived estimates of forest structure, fine‐resolution topographic diversity, and careful consideration of biogeographical differences within and among biomes is needed to accurately map biodiversity variation from above.

Gut and faecal bacterial community of the terrestrial isopod Porcellionides pruinosus: potential use for monitoring exposure scenarios - Jacinta M. M. Oliveira; Isabel Henriques; Daniel S. Read; Hyun S. Gweon; Rui G. Morgado; Sara Peixoto; António Correia; Amadeu M. V. M. Soares; Susana Loureiro (Ecotoxicology, 2021)

Adult male Cuvier's beaked whales ( Ziphius cavirostris ) engage in prolonged bouts of synchronous diving - William R. Cioffi; Nicola J. Quick; Heather J. Foley; Danielle M. Waples; Zachary T. Swaim; Jeanne M. Shearer; Daniel L. Webster; Ari S. Friedlaender; Brandon L. Southall; Robin W. Baird; Douglas P. Nowacek; Andrew J. Read (Marine Mammal Science, 2021)
Studies of the social behavior of Cuvier's beaked whales ( Ziphius cavirostris ) are challenging because of their deep‐water habitat usually far from shore and the limited time they spend at the surface. The sociality of these deepest diving mammals is of interest, however, especially for our understanding of how social systems evolve in extreme habitats. High levels of scarring suggest that males compete agonistically for access to females and so we predicted that associations among adult males would be unstable due to competitive exclusion. We tested this prediction by evaluating the diving behavior of animals within social groups off Cape Hatteras, North Carolina, considering diving synchrony a proxy for group membership. Using data from satellite‐linked depth‐recording tags, we found that adult male–male pairs showed extended periods of synchrony in diving behavior, while all pairs that included an adult male with an individual of another age and/or sex dove synchronously for less than a day. We assessed three hypotheses to explain these surprising results: sexual segregation; extended bouts of male–male competition; and the presence of male alliances. Finally, we considered testable predictions to distinguish among these explanations.

Exploring movement patterns and changing distributions of baleen whales in the western North Atlantic using a decade of passive acoustic data - Genevieve E. Davis; Mark F. Baumgartner; Peter J. Corkeron; Joel Bell; Catherine Berchok; Julianne M. Bonnell; Jacqueline Bort Thornton; Solange Brault; Gary A. Buchanan; Danielle M. Cholewiak; Christopher W. Clark; Julien Delarue; et al. (Global Change Biology, 2020)
Six baleen whale species are found in the temperate western North Atlantic Ocean, with limited information existing on the distribution and movement patterns for most. There is mounting evidence of distributional shifts in many species, including marine mammals, likely because of climate‐driven changes in ocean temperature and circulation. Previous acoustic studies examined the occurrence of minke ( Balaenoptera acutorostrata ) and North Atlantic right whales (NARW; Eubalaena glacialis ). This study assesses the acoustic presence of humpback ( Megaptera novaeangliae ), sei ( B. borealis ), fin ( B. physalus ), and blue whales ( B. musculus ) over a decade, based on daily detections of their vocalizations. Data collected from 2004 to 2014 on 281 bottom‐mounted recorders, totaling 35,033 days, were processed using automated detection software and screened for each species' presence. A published study on NARW acoustics revealed significant changes in occurrence patterns between the periods of 2004–2010 and 2011–2014; therefore, these same time periods were examined here. All four species were present from the Southeast United States to Greenland; humpback whales were also present in the Caribbean. All species occurred throughout all regions in the winter, suggesting that baleen whales are widely distributed during these months. Each of the species showed significant changes in acoustic occurrence after 2010. Similar to NARWs, sei whales had higher acoustic occurrence in mid‐Atlantic regions after 2010. Fin, blue, and sei whales were more frequently detected in the northern latitudes of the study area after 2010. Despite this general northward shift, all four species were detected less on the Scotian Shelf area after 2010, matching documented shifts in prey availability in this region. A decade of acoustic observations have shown important distributional changes over the range of baleen whales, mirroring known climatic shifts and identifying new habitats that will require further protection from anthropogenic threats like fixed fishing gear, shipping, and noise pollution.

Beyond counts and averages: Relating geodiversity to dimensions of biodiversity - Quentin D. Read; Phoebe L. Zarnetske; Sydne Record; Kyla M. Dahlin; Jennifer K. Costanza; Andrew O. Finley; Keith D. Gaddis; John M. Grady; Martina L. Hobi; Andrew M. Latimer; Sparkle L. Malone; Scott V. Ollinger; et al. (Global Ecology and Biogeography, 2020)
Aim We may be able to buffer biodiversity against the effects of ongoing climate change by prioritizing the protection of habitat with diverse physical features (high geodiversity) associated with ecological and evolutionary mechanisms that maintain high biodiversity. Nonetheless, the relationships between biodiversity and habitat vary with spatial and biological context. In this study, we compare how well habitat geodiversity (spatial variation in abiotic processes and features) and climate explain biodiversity patterns of birds and trees. We also evaluate the consistency of biodiversity–geodiversity relationships across ecoregions. Location Contiguous USA. Time period 2007–2016. Taxa studied Birds and trees. Methods We quantified geodiversity with remotely sensed data and generated biodiversity maps from the Forest Inventory and Analysis and Breeding Bird Survey datasets. We fitted multivariate regressions to alpha, beta and gamma diversity, accounting for spatial autocorrelation among Nature Conservancy ecoregions and relationships among taxonomic, phylogenetic and functional biodiversity. We fitted models including climate alone (temperature and precipitation), geodiversity alone (topography, soil and geology) and climate plus geodiversity. Results A combination of geodiversity and climate predictor variables fitted most forms of bird and tree biodiversity with Main conclusions Although climatic predictors tended to have larger individual effects than geodiversity, adding geodiversity improved climate‐only models of biodiversity. Geodiversity was correlated with biodiversity more consistently than with climate across ecoregions, but models tended to have a poor fit in ecoregions held out of the training dataset. Patterns of geodiversity could help to prioritize conservation efforts within ecoregions. However, we need to understand the underlying mechanisms more fully before we can build models transferable across ecoregions.

Exploring the internal and external wildlife gradients created by conservation fences - Katherine E. Moseby; Hugh McGregor; Brydie M. Hill; John L. Read (Conservation Biology, 2020)
Spillover effects are an expansion of conservation benefits beyond protected areas through dispersal of species that reside within. They have been well documented in marine but not terrestrial systems. To understand the effects on wildlife created by conservation fences, we explored the internal and external gradients of activity in mammal, reptile, and bird species at a conservation reserve in arid Australia that is fenced to exclude invasive rabbits ( Oryctolagus cuniculus ), cats ( Felis catus ), and foxes ( Vulpes vulpes ). Two methods were used: counts of animal tracks along transects on sand dunes and captures at pitfall‐trapping sites. In both cases, sites were spaced at different distances from the reserve fenceline inside and outside the reserve. We recorded a range of spillover, source‐sink, step, and barrier effects that combined to create a zone within and around the reserve with fence‐induced species‐specific wildlife gradients. Two endemic rodents but none of the 4 mammal species reintroduced to the reserve showed positive spillover effects. Barrier effects, where activity was highest close to the fence, were recorded for the feral cat and native bettong ( Bettongia lesueur ), species that could not breach the fence. In comparison, some reptiles and native mammal species that could permeate the fence displayed source‐sink effects; that is, their activity levels were reduced close to the fence likely due to constant emigration to the side with lower density. Activity of some reptiles was lowest at sites inside the reserve and gradually increased at outside sites with distance from the fence, a gradient likely related to trophic cascades triggered by predator exclusion. Our result shows that fenced reserves can create overlapping layers of species‐specific gradients related to each species’ ability to permeate the fence and its varying susceptibility to threats. Managers should be aware that these gradients may extend for several kilometers either side of the fence and that not all contained species will increase in abundance. Creating wider conservation benefits may require increased fence permeability and threat reduction outside the fence.

Assessing Nearshore Nekton Abundance, Substrate, and Environmental Conditions in the Northern Gulf of Mexico: Are There Differences Among Three Adjacent Coastal Areas and Have There Been Changes over Three Decades (1986–2015)? - Martin T. O’Connell; Mark S. Peterson; Sean P. Powers; Ann M. Uzee-O’Connell; E. John Anderson; J. Read Hendon (Estuaries and Coasts, 2019)

Bioengineering a Future Free of Marine Plastic Waste - Maya U. Sheth; Sarah K. Kwartler; Emma R. Schmaltz; Sarah M. Hoskinson; E. J. Martz; Meagan M. Dunphy-Daly; Thomas F. Schultz; Andrew J. Read; William C. Eward; Jason A. Somarelli (Frontiers in Marine Science, 2019)

Likely annual calving in the vaquita, Phocoena sinus : A new hope? - Barbara L. Taylor; Randall S. Wells; Paula A. Olson; Robert L. Brownell; Frances M. D. Gulland; Andrew J. Read; Francisco J. Valverde‐Esparza; Oscar H. Ortiz‐García; Diego Ruiz‐Sabio; Armando M. Jaramillo‐Legorreta; Edwyna Nieto‐Garcia; Gustavo Cardenas‐Hinojosa; et al. (Marine Mammal Science, 2019)

Scavenging in the Anthropocene: Human impact drives vertebrate scavenger species richness at a global scale - Esther Sebastián‐González; Jomar Magalhães Barbosa; Juan M. Pérez‐García; Zebensui Morales‐Reyes; Francisco Botella; Pedro P. Olea; Patricia Mateo‐Tomás; Marcos Moleón; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; Ainara Cortés‐Avizanda; et al. (Global Change Biology, 2019)
Understanding the distribution of biodiversity across the Earth is one of the most challenging questions in biology. Much research has been directed at explaining the species latitudinal pattern showing that communities are richer in tropical areas; however, despite decades of research, a general consensus has not yet emerged. In addition, global biodiversity patterns are being rapidly altered by human activities. Here, we aim to describe large‐scale patterns of species richness and diversity in terrestrial vertebrate scavenger (carrion‐consuming) assemblages, which provide key ecosystem functions and services. We used a worldwide dataset comprising 43 sites, where vertebrate scavenger assemblages were identified using 2,485 carcasses monitored between 1991 and 2018. First, we evaluated how scavenger richness (number of species) and diversity (Shannon diversity index) varied among seasons (cold vs. warm, wet vs. dry). Then, we studied the potential effects of human impact and a set of macroecological variables related to climatic conditions on the scavenger assemblages. Vertebrate scavenger richness ranged from species‐poor to species rich assemblages (4–30 species). Both scavenger richness and diversity also showed some seasonal variation. However, in general, climatic variables did not drive latitudinal patterns, as scavenger richness and diversity were not affected by temperature or rainfall. Rainfall seasonality slightly increased the number of species in the community, but its effect was weak. Instead, the human impact index included in our study was the main predictor of scavenger richness. Scavenger assemblages in highly human‐impacted areas sustained the smallest number of scavenger species, suggesting human activity may be overriding other macroecological processes in shaping scavenger communities. Our results highlight the effect of human impact at a global scale. As species‐rich assemblages tend to be more functional, we warn about possible reductions in ecosystem functions and the services provided by scavengers in human‐dominated landscapes in the Anthropocene.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.

The Australian National Rabbit Database: 50 yr of population monitoring of an invasive species - Emilie Roy‐Dufresne; Miguel Lurgi; Stuart C. Brown; Konstans Wells; Brian Cooke; Greg Mutze; David Peacock; Phill Cassey; Dave Berman; Barry W. Brook; Susan Campbell; Tarnya Cox; et al. (Ecology, 2019)
With ongoing introductions into Australia since the 1700s, the European rabbit ( Oryctolagus cuniculus ) has become one of the most widely distributed and abundant vertebrate pests, adversely impacting Australia's biodiversity and agroeconomy. To understand the population and range dynamics of the species and its impacts better, occurrence and abundance data have been collected by researchers and citizens from sites covering a broad spectrum of climatic and environmental conditions in Australia. The lack of a common and accessible repository for these data has, however, limited their use in determining important spatiotemporal drivers of the structure and dynamics of the geographical range of rabbits in Australia. To meet this need, we created the Australian National Rabbit Database, which combines more than 50 yr of historical and contemporary survey data collected from throughout the range of the species in Australia. The survey data, obtained from a suite of complementary monitoring methods, were combined with high‐resolution weather, climate, and environmental information, and an assessment of data quality. The database provides records of rabbit occurrence (689,265 records) and abundance (51,241 records, >120 distinct sites) suitable for identifying the spatiotemporal drivers of the rabbit's distribution and for determining spatial patterns of variation in its key life‐history traits, including maximum rates of population growth. Because all data are georeferenced and date stamped, they can be coupled with information from other databases and spatial layers to explore the potential effects of rabbit occurrence and abundance on Australia's native wildlife and agricultural production. The Australian National Rabbit Database is an important tool for understanding and managing the European rabbit in its invasive range and its effects on native biodiversity and agricultural production. It also provides a valuable resource for addressing questions related to the biology, success, and impacts of invasive species more generally. No copyright or proprietary restrictions are associated with the use of this data set other than citation of this Data Paper.

Towards connecting biodiversity and geodiversity across scales with satellite remote sensing - Phoebe L. Zarnetske; Quentin D. Read; Sydne Record; Keith D. Gaddis; Stephanie Pau; Martina L. Hobi; Sparkle L. Malone; Jennifer Costanza; Kyla M. Dahlin; Andrew M. Latimer; Adam M. Wilson; John M. Grady; et al. (Global Ecology and Biogeography, 2019)
Issue Geodiversity (i.e., the variation in Earth's abiotic processes and features) has strong effects on biodiversity patterns. However, major gaps remain in our understanding of how relationships between biodiversity and geodiversity vary over space and time. Biodiversity data are globally sparse and concentrated in particular regions. In contrast, many forms of geodiversity can be measured continuously across the globe with satellite remote sensing. Satellite remote sensing directly measures environmental variables with grain sizes as small as tens of metres and can therefore elucidate biodiversity–geodiversity relationships across scales. Evidence We show how one important geodiversity variable, elevation, relates to alpha, beta and gamma taxonomic diversity of trees across spatial scales. We use elevation from NASA's Shuttle Radar Topography Mission (SRTM) and c . 16,000 Forest Inventory and Analysis plots to quantify spatial scaling relationships between biodiversity and geodiversity with generalized linear models (for alpha and gamma diversity) and beta regression (for beta diversity) across five spatial grains ranging from 5 to 100 km. We illustrate different relationships depending on the form of diversity; beta and gamma diversity show the strongest relationship with variation in elevation. Conclusion With the onset of climate change, it is more important than ever to examine geodiversity for its potential to foster biodiversity. Widely available satellite remotely sensed geodiversity data offer an important and expanding suite of measurements for understanding and predicting changes in different forms of biodiversity across scales. Interdisciplinary research teams spanning biodiversity, geoscience and remote sensing are well poised to advance understanding of biodiversity–geodiversity relationships across scales and guide the conservation of nature.

Hydration differences between the major and minor grooves of DNA revealed from heat capacity measurements - Anatoliy I. Dragan; Christopher M. Read; Colyn Crane-Robinson (European Biophysics Journal, 2019)

The prevalence of ectoparasitic barnacles discriminates stocks of Atlantic common bottlenose dolphins ( Tursiops truncatus ) at risk of entanglement in coastal gill net fisheries - Kim W. Urian; Rachel Kaufmann; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2019)

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Distribution and abundance of beaked whales (Family Ziphiidae) Off Cape Hatteras, North Carolina, U.S.A. - William A. McLellan; Ryan J. McAlarney; Erin W. Cummings; Andrew J. Read; Charles G. M. Paxton; Joel T. Bell; D. Ann Pabst (Marine Mammal Science, 2018)
Beaked whales are vulnerable to the impacts of disturbance from several sources of anthropogenic sound. Here we report the distribution and abundance of beaked whales off Cape Hatteras, North Carolina, U.S.A., an area utilized by the U.S. Navy for training exercises, and of particular interest for seismic geophysical surveys. From May 2011 through November 2015, monthly aerial surveys were conducted at the site. Beaked whales were encountered 74 times ( n = 205 individuals) during these surveys. Ziphius cavirostris , the most commonly encountered species, was observed in every month of the year. Mesoplodon spp. were encountered in ten months of the year. Photographs of adult males with erupted teeth permitted six sightings to be identified conclusively as M. europaeus ; M. mirus was also photographed just outside the study area. Beaked whale surface densities stratified by depth (0.005–0.007/km 2 ) were among the highest reported in the world for small ziphiids. A quantitative comparison of sightings and stranding records suggests that strandings do not accurately reflect the relative abundance of beaked whale species in this area. We conclude that Cape Hatteras, at the convergence of the Labrador Current and Gulf Stream, is a particularly important year‐round habitat for several species of beaked whales.

Heard but not seen: Occurrence of Kogia spp. along the western North Atlantic shelf break - Lynne E. W. Hodge; Simone Baumann‐Pickering; John A. Hildebrand; Joel T. Bell; Erin W. Cummings; Heather J. Foley; Ryan J. McAlarney; William A. McLellan; D. Ann Pabst; Zachary T. Swaim; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2018)

Survey of Citrus tristeza virus (CTV) on Citrus paradisi (Macfad.) cv. “Marsh” in South Africa - D. A. Read; M. F. Palacios; J. Figueroa; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2018)

Survey of Citrus tristeza virus (CTV) diversity in pigmented Citrus x paradisi (Macfad.) (Grapefruit) trees in north-western Argentina - D. A. Read; M. F. Palacios; J. Kleynhans; J. Figueroa; L. Foguet; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2018)

The metabolic regimes of flowing waters - E. S. Bernhardt; J. B. Heffernan; N. B. Grimm; E. H. Stanley; J. W. Harvey; M. Arroita; A. P. Appling; M. J. Cohen; W. H. McDowell; R. O. Hall; J. S. Read; B. J. Roberts; et al. (Limnology and Oceanography, 2018)
The processes and biomass that characterize any ecosystem are fundamentally constrained by the total amount of energy that is either fixed within or delivered across its boundaries. Ultimately, ecosystems may be understood and classified by their rates of total and net productivity and by the seasonal patterns of photosynthesis and respiration. Such understanding is well developed for terrestrial and lentic ecosystems but our understanding of ecosystem phenology has lagged well behind for rivers. The proliferation of reliable and inexpensive sensors for monitoring dissolved oxygen and carbon dioxide is underpinning a revolution in our understanding of the ecosystem energetics of rivers. Here, we synthesize our current understanding of the drivers and constraints on river metabolism, and set out a research agenda aimed at characterizing, classifying and modeling the current and future metabolic regimes of flowing waters.

Temporal stability and mixed-stock analyses of humpback whales (Megaptera novaeangliae) in the nearshore waters of the Western Antarctic Peninsula - G. R. Albertson; A. S. Friedlaender; D. J. Steel; A. Aguayo-Lobo; S. L. Bonatto; S. Caballero; R. Constantine; A. L. Cypriano-Souza; M. H. Engel; C. Garrigue; L. Flórez-González; D. W. Johnston; et al. (Polar Biology, 2018)

Survey of citrus tristeza virus (CTV) strains in Citrus x limon (L) Burm f. (lemon) in Tucumán Province, Argentina - D. A. Read; M. F. Palacios; J. Figueroa; L. Foguet; J. Kleynhans; B. Stein; G. Pietersen (European Journal of Plant Pathology, 2017)

Arbuscular mycorrhizas are present on Spitsbergen - K. K. Newsham; P. B. Eidesen; M. L. Davey; J. Axelsen; E. Courtecuisse; C. Flintrop; A. G. Johansson; M. Kiepert; S.E. Larsen; K. E. Lorberau; M. Maurset; J. McQuilkin; et al. (Mycorrhiza, 2017)

Seasonality of change: Summer warming rates do not fully represent effects of climate change on lake temperatures - Luke A. Winslow; Jordan S. Read; Gretchen J. A. Hansen; Kevin C. Rose; Dale M. Robertson (Limnology and Oceanography, 2017)
Responses in lake temperatures to climate warming have primarily been characterized using seasonal metrics of surface‐water temperatures such as summertime or stratified period average temperatures. However, climate warming may not affect water temperatures equally across seasons or depths. We analyzed a long‐term dataset (1981–2015) of biweekly water temperature data in six temperate lakes in Wisconsin, U.S.A. to understand (1) variability in monthly rates of surface‐ and deep‐water warming, (2) how those rates compared to summertime average trends, and (3) if monthly heterogeneity in water temperature trends can be predicted by heterogeneity in air temperature trends. Monthly surface‐water temperature warming rates varied across the open‐water season, ranging from 0.013 in August to 0.073°C yr −1 in September (standard deviation [SD]: 0.025°C yr −1 ). Deep‐water trends during summer varied less among months (SD: 0.006°C yr −1 ), but varied broadly among lakes (–0.056°C yr −1 to 0.035°C yr −1 , SD: 0.034°C yr −1 ). Trends in monthly surface‐water temperatures were well correlated with air temperature trends, suggesting monthly air temperature trends, for which data exist at broad scales, may be a proxy for seasonal patterns in surface‐water temperature trends during the open water season in lakes similar to those studied here. Seasonally variable warming has broad implications for how ecological processes respond to climate change, because phenological events such as fish spawning and phytoplankton succession respond to specific, seasonal temperature cues.

Enthalpy–entropy compensation: the role of solvation - Anatoliy I. Dragan; Christopher M. Read; Colyn Crane-Robinson (European Biophysics Journal, 2017)

Ecology under lake ice - Stephanie E. Hampton; Aaron W. E. Galloway; Stephen M. Powers; Ted Ozersky; Kara H. Woo; Ryan D. Batt; Stephanie G. Labou; Catherine M. O'Reilly; Sapna Sharma; Noah R. Lottig; Emily H. Stanley; Rebecca L. North; et al. (Ecology Letters, 2017)
Winter conditions are rapidly changing in temperate ecosystems, particularly for those that experience periods of snow and ice cover. Relatively little is known of winter ecology in these systems, due to a historical research focus on summer ‘growing seasons’. We executed the first global quantitative synthesis on under‐ice lake ecology, including 36 abiotic and biotic variables from 42 research groups and 101 lakes, examining seasonal differences and connections as well as how seasonal differences vary with geophysical factors. Plankton were more abundant under ice than expected; mean winter values were 43.2% of summer values for chlorophyll a , 15.8% of summer phytoplankton biovolume and 25.3% of summer zooplankton density. Dissolved nitrogen concentrations were typically higher during winter, and these differences were exaggerated in smaller lakes. Lake size also influenced winter‐summer patterns for dissolved organic carbon ( DOC ), with higher winter DOC in smaller lakes. At coarse levels of taxonomic aggregation, phytoplankton and zooplankton community composition showed few systematic differences between seasons, although literature suggests that seasonal differences are frequently lake‐specific, species‐specific, or occur at the level of functional group. Within the subset of lakes that had longer time series, winter influenced the subsequent summer for some nutrient variables and zooplankton biomass.

Increased incidence of bladder cancer, lymphoid leukaemia, and myeloma in a cohort of Queensland melanoma families - Jazlyn Read; Judith Symmons; Jane M. Palmer; Grant W. Montgomery; Nicholas G. Martin; Nicholas K. Hayward (Familial Cancer, 2016)

Genomewide investigation of adaptation to harmful algal blooms in common bottlenose dolphins ( Tursiops truncatus ) - Kristina M. Cammen; Thomas F. Schultz; Patricia E. Rosel; Randall S. Wells; Andrew J. Read (Molecular Ecology, 2015)
Harmful algal blooms ( HAB s), which can be lethal in marine species and cause illness in humans, are increasing worldwide. In the Gulf of Mexico, HAB s of Karenia brevis produce neurotoxic brevetoxins that cause large‐scale marine mortality events. The long history of such blooms, combined with the potentially severe effects of exposure, may have produced a strong selective pressure for evolved resistance. Advances in next‐generation sequencing, in particular genotyping‐by‐sequencing, greatly enable the genomic study of such adaptation in natural populations. We used restriction site‐associated DNA ( RAD ) sequencing to investigate brevetoxicosis resistance in common bottlenose dolphins ( Tursiops truncatus ). To improve our understanding of the epidemiology and aetiology of brevetoxicosis and the potential for evolved resistance in an upper trophic level predator, we sequenced pools of genomic DNA from dolphins sampled from both coastal and estuarine populations in Florida and during multiple HAB ‐associated mortality events. We sequenced 129 594 RAD loci and analysed 7431 single nucleotide polymorphisms ( SNP s). The allele frequencies of many of these polymorphic loci differed significantly between live and dead dolphins. Some loci associated with survival showed patterns suggesting a common genetic‐based mechanism of resistance to brevetoxins in bottlenose dolphins along the Gulf coast of Florida, but others suggested regionally specific mechanisms of resistance or reflected differences among HAB s. We identified candidate genes that may be the evolutionary target for brevetoxin resistance by searching the dolphin genome for genes adjacent to survival‐associated SNP s.

From genome-wide to candidate gene: an investigation of variation at the major histocompatibility complex in common bottlenose dolphins exposed to harmful algal blooms - Kristina M. Cammen; Lynsey A. Wilcox; Patricia E. Rosel; Randall S. Wells; Andrew J. Read (Immunogenetics, 2015)

A quantitative analysis of the response of short‐finned pilot whales, Globicephala macrorhynchus , to biopsy sampling - Danielle D. Crain; Ari S. Friedlaender; Dave W. Johnston; Doug P. Nowacek; Bethany L. Roberts; Kim W. Urian; Danielle M. Waples; Andrew J. Read (Marine Mammal Science, 2014)

Including cetaceans in multi-species assessment models using strandings data: why, how and what can we do about it? - Saavedra Camilo; Cabrero Agueda; Cedeira Jose; Cerviño Santiago; Gago Jesus; González-Nuevo Gonzalo; Howell Daniel; López Alfredo; Pierce Graham; Read Fiona; Santos M. Begoña (Frontiers in Marine Science, 2014)

Ecological niche segregation among five toothed whale species off the NW Iberian Peninsula using ecological tracers as multi-approach - Paula Méndez-Fernandez; Graham J. Pierce; Paco Bustamante; Tiphaine Chouvelon; Marisa Ferreira; Angel F. González; Alfredo López; Fiona L. Read; M. Begoña Santos; Jérôme Spitz; José V. Vingada; Florence Caurant (Marine Biology, 2013)

Biological markers of exposure to organophosphorus nerve agents - Robin M. Black; Robert W. Read (Archives of Toxicology, 2013)

Assessment and management of old-growth forests in south eastern Australia - Rodney J. Keenan; Steve M. Read (Plant Biosystems, 2012)

Phytoplankton distribution and nitrogen dynamics in the southwest indian subtropical gyre and Southern Ocean waters - S. J. Thomalla; H. N. Waldron; M. I. Lucas; J. F. Read; I. J. Ansorge; E. Pakhomov (Ocean Science, 2011)
During the 1999 Marion Island Oceanographic Survey (MIOS 4) in late austral summer, a northbound and reciprocal southbound transect were taken along the Southwest Indian and Madagascar Ridge, between the Prince Edward Islands and 31° S. The sections crossed a number of major fronts and smaller mesoscale features and covered a wide productivity spectrum from subtropical to subantarctic waters. Associated with the physical survey were measurements of size fractionated chlorophyll, nutrients and nitrogen (NO3, NH4 and urea) uptake rates. Subtropical waters were characterised by low chlorophyll concentrations (max = 0.27.3 mg m−3 dominated by pico-phytoplankton cells (> 81%) and very low f-ratios (

Seasonal characteristics of tropical marine boundary layer air measured at the Cape Verde Atmospheric Observatory - L. J. Carpenter; Z. L. Fleming; K. A. Read; J. D. Lee; S. J. Moller; J. R. Hopkins; R. M. Purvis; A. C. Lewis; K. Müller; B. Heinold; H. Herrmann; K. Wadinga Fomba; et al. (Journal of Atmospheric Chemistry, 2010)

Widespread omnivory and low temporal and spatial variation in the diet of fishes in a hydrologically variable northern Australian river - B. J. Pusey; A. H. Arthington; B. Stewart‐Koster; M. J. Kennard; M. G. Read (Journal of Fish Biology, 2010)
This article examines the trophic ecology of freshwater fishes (22 species in 15 families) in a wet and dry tropical Australian river of high intra‐annual and interannual hydrological variability. Seven major trophic groups were identified by cluster analysis; however, four food items (filamentous algae, chironomid larvae, Trichoptera larvae and Ephemeroptera nymphs) comprised almost half of the average diet of all species. The influence of species, fish size, spatial effects and temporal effects on food use was investigated using redundancy analysis. Size, time and space accounted for little of the perceived variation. Ontogenetic changes in diet were minor and limited to a few large species. Spatial variation in trophic composition of the fish assemblages reflected the effects of the Burdekin Falls and dam, a major geographic barrier, on species distributions. Little spatial variation in diet was detected after accounting for this biogeographical effect. Temporal variations in flow, although marked, had little effect on variations in fish diet composition due to the low temporal diversity of food resources in physically monotonous sand and gravel channels. Species identity accounted for

Biomarkers of organophosphorus nerve agent exposure: comparison of phosphylated butyrylcholinesterase and phosphylated albumin after oxime therapy - Robert W. Read; James R. Riches; Jacqueline A. Stevens; Sarah J. Stubbs; Robin M. Black (Archives of Toxicology, 2010)

Multiple sightings of large groups of Arnoux's beaked whales (Berardius arnouxii) in the Gerlache Strait, Antarctica - Ari S. Friedlaender; Douglas P. Nowacek; David W. Johnston; Andrew J. Read; Reny B. Tyson; Lindsey Peavey; Eletta M. S. Revelli (Marine Mammal Science, 2009)

A Robust Technique for Mapping Vegetation Condition Across a Major River System - S. C. Cunningham; R. Mac Nally; J. Read; P. J. Baker; M. White; J. R. Thomson; P. Griffioen (Ecosystems, 2009)

Cyclone Effects on the Structure and Production of a Tropical Upland Rainforest: Implications for Life-History Tradeoffs - Sean M. Gleason; Laura J. Williams; Jennifer Read; Daniel J. Metcalfe; Patrick J. Baker (Ecosystems, 2008)

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Current Practices and Future Opportunities for Policy on Climate Change and Invasive Species - CHRISTOPHER R. PYKE; ROXANNE THOMAS; READ D. PORTER; JESSICA J. HELLMANN; JEFFREY S. DUKES; DAVID M. LODGE; GABRIELA CHAVARRIA (Conservation Biology, 2008)
Climate change and invasive species are often treated as important, but independent, issues. Nevertheless, they have strong connections: changes in climate and societal responses to climate change may exacerbate the impacts of invasive species, whereas invasive species may affect the magnitude, rate, and impact of climate change. We argue that the design and implementation of climate‐change policy in the United States should specifically consider the implications for invasive species; conversely, invasive‐species policy should address consequences for climate change. The development of such policies should be based on (1) characterization of interactions between invasive species and climate change, (2) identification of areas where climate‐change policies could negatively affect invasive‐species management, and (3) identification of areas where policies could benefit from synergies between climate change and invasive‐species management.

Leptotrichia endocarditis: Report of two cases from the International Collaboration on Endocarditis (ICE) database and review of previous cases - L. B. Caram; J. P. Linefsky; K. M. Read; D. R. Murdoch; T. Lalani; C. W. Woods; L. B. Reller; S. S. Kanj; M. M. Premru; S. Ryan; M. Al-Hegelan; P. Y. Donnio; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

INVITED REVIEW: Molecular analysis of predation: a review of best practice for DNA‐based approaches - R. A. KING; D. S. READ; M. TRAUGOTT; W. O. C. SYMONDSON (Molecular Ecology, 2008)
Molecular analysis of predation, through polymerase chain reaction amplification of prey remains within the faeces or digestive systems of predators, is a rapidly growing field, impeded by a lack of readily accessible advice on best practice. Here, we review the techniques used to date and provide guidelines accessible to those new to this field or from a different molecular biology background. Optimization begins with field collection, sample preservation, predator dissection and DNA extraction techniques, all designed to ensure good quality, uncontaminated DNA from semidigested samples. The advantages of nuclear vs. mitochondrial DNA as primer targets are reviewed, along with choice of genes and advice on primer design to maximize specificity and detection periods following ingestion of the prey by the predators. Primer and assay optimization are discussed, including cross‐amplification tests and calibratory feeding experiments. Once primers have been made, the screening of field samples must guard against (through appropriate controls) cross contamination. Multiplex polymerase chain reactions provide a means of screening for many different species simultaneously. We discuss visualization of amplicons on gels, with and without incorporation of fluorescent primers. In more specialized areas, we examine the utility of temperature and denaturing gradient gel electrophoresis to examine responses of predators to prey diversity, and review the potential of quantitative polymerase chain reaction systems to quantify predation. Alternative routes by which prey DNA might get into the guts of a predator (scavenging, secondary predation) are highlighted. We look ahead to new technologies, including microarrays and pyrosequencing, which might one day be applied to this field.

Comparing Effectiveness of Experimental and Implemented Bycatch Reduction Measures: the Ideal and the Real - T. M. COX; R. L. LEWISON; R. ŽYDELIS; L. B. CROWDER; C. SAFINA; A. J. READ (Conservation Biology, 2007)
Fishers, scientists, and resource managers have made substantial progress in reducing bycatch of sea turtles, seabirds, and marine mammals through physical modifications to fishing gear. Many bycatch‐avoidance measures have been developed and tested successfully in controlled experiments, which have led to regulated implementation of modified or new fishing gear. Nevertheless, successful bycatch experiments may not translate to effective mitigation in commercial fisheries because experimental conditions are relaxed in commercial fishing operations. Such a difference between experimental results and real‐world results with fishing fleets may have serious consequences for management and conservation of protected species taken as bycatch. We evaluated preimplementation experimental measures and postimplementation efficacy from primary and gray literature for three case studies: acoustic pingers that warn marine mammals of the presence of gill nets, turtle excluder devices that reduce bycatch of turtles in trawls, and various measures to reduce seabird bycatch in longlines. Three common themes to successful implementation of bycatch reduction measures are long‐standing collaborations among the fishing industry, scientists, and resource managers; pre‐ and postimplementation monitoring; and compliance via enforcement and incentives.

Stochasticity generates an evolutionary instability for infectious disease - Jonathan M. Read; Matt J. Keeling (Ecology Letters, 2007)
Traditional models of disease evolution are based upon the deterministic competition between strains that confer complete cross‐immunity, and predict the selection of strains with higher basic reproductive ratios ( R 0 ). In contrast, evolution in a stochastic setting is determined by a complex mixture of influences. Here, to isolate the impact of stochasticity, we constrain all competing strains to have an equal basic reproductive ratio – thereby eliminating deterministic selection. The resulting stochastic models predict an evolutionary unstable strategy, which separates a region favouring the evolution of rapid‐transmission (acute) strains from one favouring persistent (chronic) strains. We find this to be a generic phenomenon with strain evolution consistently driven towards extremes of epidemiological behaviour. Even in the absence of an equal R 0 constraint, such stochastic selective pressures operate in addition to standard deterministic selection and will therefore influence the evolutionary behaviour of disease in all scenarios.

Phosphylated tyrosine in albumin as a biomarker of exposure to organophosphorus nerve agents - Nichola H. Williams; John M. Harrison; Robert W. Read; Robin M. Black (Archives of Toxicology, 2007)

An eddy covariance mesonet to measure the effect of forest age on land–atmosphere exchange - MICHAEL L. GOULDEN; GREGORY C. WINSTON; ANDREW M. S. McMILLAN; MARCY E. LITVAK; EDWARD L. READ; ADRIAN V. ROCHA; J. ROB ELLIOT (Global Change Biology, 2006)
We deployed a mesonet of year‐round eddy covariance towers in boreal forest stands that last burned in ∼1850, ∼1930, 1964, 1981, 1989, 1998, and 2003 to understand how CO 2 exchange and evapotranspiration change during secondary succession. We used MODIS imagery to establish that the tower sites were representative of the patterns of secondary succession in the region, and Landsat images to show that the individual stands have changed over the last 22 years in ways that match the spatially derived trends. The eddy covariance towers were well matched, with similar equipment and programs, which maximized site‐to‐site precision and allowed us to operate the network in an efficient manner. The six oldest sites were fully operational for ∼90% of the growing season and ∼70% of the dormant season from 2001 or 2002 to 2004, with most of the missing data caused by low battery charge or bad signals from the sonic anemometers. The rates of midday growing‐season CO 2 uptake recovered to preburn levels within 4 years of fire. The seasonality of land–atmosphere exchange and growing‐season length changed markedly with stand age. The foliage in the younger stands (1989, 1998, and 2003 burns) was almost entirely deciduous, which resulted in comparatively short growing seasons that lasted ∼65 days. In contrast, the older stands (1850, 1930, 1964, and 1981) were mostly evergreen, which resulted in comparatively long growing seasons that lasted ∼130 days. The eddy covariance mesonet approach we describe could be used within the context of other ecological experimental designs such as controlled manipulations and gradient comparisons.

Molecular detection of predation by soil micro‐arthropods on nematodes - D. S. READ; S. K. SHEPPARD; M. W. BRUFORD; D. M. GLEN; W. O. C. SYMONDSON (Molecular Ecology, 2006)
The relative importance of the factors driving change in the population dynamics of nematodes in the soil is almost completely unknown. Top‐down control by micro‐arthropod predators may have a significant impact on nematode population dynamics. We report experiments showing that mites and Collembola were capable of reducing nematode numbers in the laboratory and were feeding on a targeted nematode species in the field. A PCR‐based approach was developed for the detection of predation on three species of slug‐ and insect‐pathogenic nematodes: Phasmarhabditis hermaphrodita , Heterorhabditis megidis and Steinernema feltiae . The collembolan Folsomia candida and the mesostigmatid mite Stratiolaelaps miles were employed as model predators to calibrate post‐ingestion prey DNA detection times. Fragments of cytochrome oxidase I (COI) mtDNA were sequenced and species‐specific primers were designed, amplifying 154‐, 154‐ and 203‐bp fragments for each of the nematode species. Detection times for nematode DNA within the guts of Collembola were longer than in mites, with half‐lives (50% of samples testing positive) of 08.75 h and 05.03 h, respectively. F. candida significantly reduced numbers of the nematode H. megidis , with rates of predation of ∼0.4 nematode infective juveniles per collembolan per hour over 10 h. Four taxa of field‐caught micro‐arthropod that had been exposed to the nematode P. hermaphrodita for a period of 12 h were analysed and significant numbers of three taxa tested positive. This is the first application of PCR techniques for the study of nematophagy and the first time these techniques have been used to measure predation on nematodes in the field.

The mycorrhizal community in a forest chronosequence of Sitka spruce [Picea sitchensis (Bong.) Carr.] in Northern England - Götz Palfner; M. Angélica Casanova-Katny; David J. Read (Mycorrhiza, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Abnormal gonadal morphology in intersex, Echinogammarus marinus (Amphipoda): a possible cause of reduced fecundity? - A. T. Ford; T. P. Rodgers-Gray; I. M. Davies; A. M. Dunn; P. A. Read; C. D. Robinson; J. E. Smith; T. F. Fernandes (Marine Biology, 2005)

Experimental designs suitable for testing many factors with limited number of explants in tissue culture - Mehmet Nuri Nas; Kent M. Eskridge; Paul E. Read (Plant Cell, Tissue and Organ Culture (PCTOC), 2005)

The costs of intersexuality: a crustacean perspective - A. T. Ford; T. F. Fernandes; P. A. Read; C. D. Robinson; I. M. Davies (Marine Biology, 2004)

Estimating soil carbon fluxes following land‐cover change: a test of some critical assumptions for a region in Costa Rica - Jennifer S. Powers; Jane M. Read; Julie S. Denslow; Sandra M. Guzman (Global Change Biology, 2004)
Changes in soil carbon storage that accompany land‐cover change may have significant effects on the global carbon cycle. The objective of this work was to examine how assumptions about preconversion soil C storage and the effects of land‐cover change influence estimates of regional soil C storage. We applied three models of land‐cover change effects to two maps of preconversion soil C in a 140 000 ha area of northeastern Costa Rica. One preconversion soil C map was generated using values assigned to tropical wet forest from the literature, the second used values obtained from extensive field sampling. The first model of land‐cover change effects used values that are typically applied in global assessments, the second and third models used field data but differed in how the data were aggregated (one was based on land‐cover transitions and one was based on terrain attributes). Changes in regional soil C storage were estimated for each combination of model and preconversion soil C for three time periods defined by geo‐referenced land‐cover maps. The estimated regional soil C under forest vegetation (to 0.3 m) was higher in the map based on field data (10.03 Tg C) than in the map based on literature data (8.90 Tg C), although the range of values derived from propagating estimation errors was large (7.67–12.40 Tg C). Regional soil C storage declined through time due to forest clearing for pasture and crops. Estimated CO 2 fluxes depended more on the model of land‐cover change effects than on preconversion soil C. Cumulative soil C losses (1950–1996) under the literature model of land‐cover effects exceeded estimates based on field data by factors of 3.8–8.0. In order to better constrain regional and global‐scale assessments of carbon fluxes from soils in the tropics, future research should focus on methods for extrapolating regional‐scale constraints on soil C dynamics to larger spatial and temporal scales.

Quantifying mortality of tropical rain forest trees using high‐spatial‐resolution satellite data - David B. Clark; Carlomagno Soto Castro; Luis Diego Alfaro Alvarado; Jane M. Read (Ecology Letters, 2004)
Assessment of forest responses to climate change is severely hampered by the limited information on tree death on short temporal and broad spatial scales, particularly in tropical forests. We used 1‐m resolution panchromatic IKONOS and 0.7‐m resolution QuickBird satellite data, acquired in 2000 and 2002, respectively, to evaluate tree death rates at the La Selva Biological Station in old‐growth Tropical Wet Forest in Costa Rica, Central America. Using a calibration factor derived from ground inspection of tree deaths predicted from the images, we calculated a landscape‐scale annual exponential death rate of 2.8%. This corresponds closely to data for all canopy‐level trees in 18 forest inventory plots, each of 0.5 ha, for a mostly‐overlapping 2‐year period (2.8% per year). This study shows that high‐spatial‐resolution satellite data can now be used to measure old‐growth tropical rain forest tree death rates, suggesting many new avenues for tropical forest ecology and global change research.

Identification of differentially expressed genes in shrimp (Penaeus stylirostris) infected with White spot syndrome virus by cDNA microarrays - A. K. Dhar; A. Dettori; M. M. Roux; K. R. Klimpel; B. Read (Archives of Virology, 2003)

Non-invasive imaging of roots with high resolution X-ray micro-tomography - P.J. Gregory; D. J. Hutchison; D. B. Read; P. M. Jenneson; W. B. Gilboy; E. J. Morton (Plant and Soil, 2003)

ABUNDANCE OF BOTTLENOSE DOLPHINS IN THE BAYS, SOUNDS, AND ESTUARIES OF NORTH CAROLINA - Andrew J. Read; Kim W. Urian; Ben Wilson; Danielle M. Waples (Marine Mammal Science, 2003)
A bstract We conducted a mark‐recapture survey of bottlenose dolphins Tursiops truncatus in the bays, sounds, and estuaries of North Carolina during July 2000, using photographic identification techniques. During this survey we took 7,682 photographs of dolphins and, of these, 3,457 images were of sufficient quality for analysis. We identified 306 dolphins from distinctive nicks and notches on their dorsal fins. Eighry‐six dolphins were photographed on more than one occasion during the course of the survey; one dolphin was photographed on four separate days. We then applied the results of our photographic analyses to several mark‐recapture models and examined potential violations of the assumptions of these models, including an unexpected correlation between photo quality and mark distinctiveness. Our analysis suggests that our results are robusr to possible violations of these assumptions. The resulting estimates were then scaled to account for the proportion (0.46) of unmarked dolphins in the population. Our best estimate of the number of dolphins present in the inshore waters of North Carolina during July 2000 is 1,033 with a 95% Confidence Interval of 860–1,266 (CV = 0.099). Most dolphins were found in the northern part of the study area, which includes the second largest estuarine system in the United States.

Evaluation in barley lines of a simple pollen method for breeding for drought tolerance in wheat - James M. Morgan; John F. Holland; Barbara J. Read (Cereal Research Communications, 2002)

Structural and floristic characteristics of some monodominant and adjacent mixed rainforests in New Caledonia - J. Read; T. Jaffré; E. Godrie; G. S. Hope; J.‐M. Veillon (Journal of Biogeography, 2000)
Nothofagus spp. dominate the upper canopy of some rainforests on ultramafic soils in New Caledonia. These monodominant forests typically occur within, or contiguous with, larger areas of mixed‐canopy rainforest. In this study the structure, diversity and composition of six Nothofagus ‐dominated plots were investigated, and comparisons were made with three adjacent mixed rainforest plots. Stand density and basal area (all stems ≥ 1.3 m high) in the Nothofagus plots were in the range 16,056–27,550 stems/ha and 43.1–69.9 m 2 /ha, respectively. There was no significant difference ( P ≥ 0.05) in total stand density or basal area between the paired Nothofagus and mixed rainforests, but there were consistently fewer trees and less basal area of trees ≥ 40 cm d.b.h. in the Nothofagus forests. Species richness, species diversity (Shannon‐Wiener, based on basal area) and equitability (based on basal area) of trees ≥ 20 cm d.b.h. on 0.1 ha Nothofagus plots were in the range 4–17, 0.96–3.76 and 0.45–0.87, respectively. No significant differences ( P ≥ 0.05) were recorded in these three parameters between the paired Nothofagus and mixed rainforests, although species diversity was consistently lower in the paired Nothofagus forests. Comparison of dominance by density and basal area indicated that although the uppermost canopy of the Nothofagus forests was dominated by Nothofagus (70–95%), the basal area and density contribution was ≤ 55% except at Col de Yaté (≈ 85%). Analysis of similarity indicated no significant difference in stand composition of trees ≥ 20 cm d.b.h. (following removal of Nothofagus from the data set) between Nothofagus and mixed rainforests using basal area, density or presence‐absence data. It is concluded that the Nothofagus ‐dominated forests differ from the adjacent mixed rainforests mainly by (1) dominance of the uppermost canopy , without necessarily dominance of the stand by basal area or density, and (2) the smaller basal area contributed by large trees (all species).

Invertase activity as affected by cytokinin-like compounds during potato tuberizationin vitro - Servet Kefi; Alexander D. Pavlista; Michael M. Meagher; Paul E. Read (American Journal of Potato Research, 2000)

Role of a callose synthase zymogen in regulating wall deposition in pollen tubes of Nicotiana alata Link et Otto - Huijuan Li; Antony Bacic; Steve M. Read (Planta, 1999)

Phenylalanine kinetics are associated with tardive dyskinesia in men but not in women - M. A. Richardson; Margaret A. Reilly; Laura L. Read; Cheryl J. Flynn; Raymond F. Suckow; Timothy J. Maher; Istvan Sziraki (Psychopharmacology, 1999)

Branched chain amino acids decrease tardive dyskinesia symptoms - M. A. Richardson; Margaret L. Bevans; Josephine B. Weber; Janet J. Gonzalez; Cheryl J. Flynn; Leora Amira; Laura L. Read; Raymond F. Suckow; Timothy J. Maher (Psychopharmacology, 1999)

The interaction of sarin and soman with plasma proteins: the identification of a novel phosphonylation site - Robin M. Black; John M. Harrison; Robert W. Read (Archives of Toxicology, 1999)

Subcellular distribution of arabinogalactan proteins in pollen grains and tubes as revealed with a monoclonal antibody raised against stylar arabinogalactan proteins - C. Ferguson; A. Bacic; M. A. Anderson; S. M. Read (Protoplasma, 1999)

Location of cellulose and callose in pollen tubes and grains of Nicotiana tabacum - C. Ferguson; T. T. Teeri; M. Siika-aho; S. M. Read; A. Bacic (Planta, 1998)

Invertebrates in Woodlands Polluted by Heavy Metals – – An Evaluation Using Canonical Correspondence Analysis - Helen J. Read; M. H. Martin; J. M. V. Rayner (Water, Air, & Soil Pollution, 1998)

MONITORING A REHABILITATED HARBOR PORPOISE USING SATELLITE TELEMETRY - Andrew J. Westgate; Andrew J. Read; Tara M. Cox; T. David Schofield; Brent R. Whitaker; Kurt E. Anderson (Marine Mammal Science, 1998)

Membrane fractionation and enrichment of callose synthase from pollen tubes of Nicotiana alata Link et Otto - Adrian Turner; Antony Bacic; Philip J. Harris; Steve M. Read (Planta, 1998)

Steady Infiltration in Sloping Porous Domains: the Onset of Saturation - Peter Tritscher; Philip Broadbridge; Janine M. Stewart; W. Wayne Read (Transport in Porous Media, 1998)

Linkage disequilibrium studies in multiple endocrine neoplasia type 1 (MEN1) - J. H. D. Bassett; A. A. J. Pannett; S. A. Forbes; R. V. Thakker; M. McCarthy; A. P. Read; B. T. Teh; C. Larsson; S. Kytl; J. Leisti; P. Salmela; G. Weber; et al. (Human Genetics, 1997)

Role of topography sensing for infection-structure differentiation in cereal rust fungi - Nick D. Read; Lesley J. Kellock; Tony J. Collins; Alan M. Gundlach (Planta, 1997)

Anomalous biochemical responses in tests of the delayed neuropathic potential of methamidophos (O,S-dimethyl phosphorothioamidate), its resolved isomers and of some higher O-alkyl homologues - M. K. Johnson; E. Vilanova; D. J. Read (Archives of Toxicology, 1991)

Assessment of chemical toxicity using mammalian mitochondrial electron transport particles - L. M. Knobeloch; G. A. Blondin; H. W. Read; J. M. Harkin (Archives of Environmental Contamination and Toxicology, 1990)